The Effectiveness of Motivational Interviewing Counseling to Improve Psychological Well-Being on Students with Online Game Addiction Tendency: Array - Mayang T Afriwilda; Mulawarman Mulawarman (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2021)
Psychological well-being is a condition of a person who is not only free from pressure or mental problems but a mental condition that is considered healthy and functioning optimally. This study aims to determine the strength-based counseling intervention based on motivational interviewing to improve psychological well-being. This study uses an experiment with a pretest-posttest control group design. 32 eleventh-grade students in high schools in the city of Semarang involved as participants. Participants were selected using purposive sampling (low psychological well-being and online game tendency), then divided into a control group and an experimental group. The results showed that during the measurement period pre-test, post-test, and follow-up here was a significant difference (t = -9.670, p > .05) in the experimental group, while in the control group (t = -7.936, p > .05). It can be said that when viewed from the pre-test, post-test, and follow-up intervention the use of motivational interviewing to increase the level of psychological well-being is more significant than the intervention in the control group. As the result, there is a significant change in student's psychological well-being after counseling with motivational interviewing.